Social media addiction and usage purposes as predictors of eating behaviors, eating disorders and orthorexia nervosa: a study on young adults - Hamurcu, Pınar (Journal of Dependence, 2023)
Objective: The aim of this study was to examine social media addiction and social media usage purposes as predictors of eating behaviors, eating disorders risk and orthorexia disposition in university students.Method: In this cross-sectional descriptive study, 752 students who enrolled in Uskudar University 2020-2021 academic year participated. Data was collected voluntarily with diagnostic form, Social Media Addiction Scale (SMAS), Aims of Social Network Sites Usage Scale (ASNSUS), SCOFF Eating Disorders Scale, Orthorexia-15 Questionnaire (ORTO-15) and Three-Factor Eating Scale (TFEQ-R21), were created in Google Forms and applied online.Results: A total of 752 university students participated and 73% were female. The mean age was 20,94±2,80 years, and the mean body mass index (BMI) was 22,57±3,41 kg/m2. In this study, 44.3% of the students spent 3-5 hours/day on social media. The most frequently used (91.6%) and the most time-spent (80.7%) social network was Instagram. Eating disorders risk were found in 23.3% and orthorexia disposition were found in 53.2% of the students. Significant correlations were found between TFEQ-R21 and ORTO-15 with ASNSUS and SMAS, and also SCOFF with SMAS. In addition, students' social network usage purposes and social media addictions significantly predicted eating behaviors, risk of eating disorders and orthorexia disposition.Conclusion: Social network usage purposes and social media addiction were found to be a significant predictors of eating behaviors, eating disorders risk and orthorexia disposition.
Keywords: Social media; feeding behavior; feeding and eating disorders